Maternal Characteristics Associated with stunting Incidence: A Cross-Sectional Study - nafisah, khilda durrotun; Christiana, Indah (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2025)
Background: In Indonesia, stunting remains a very serious challenge for public health development. Nationally, the stunting prevalence in 2023 was 21.6% which was still above the threshold set by WHO. Purpose: This study aimed to analyze maternal characteristics with stunting occurrence at Puskesmas Air Periukan. Methods: The study used a quantitative analytical approach with a cross-sectional design. The target population comprised all mothers with toddlers aged between 6 and 59 months. The sample were 65 mothers that were selected using purposive sampling technique. Questionnaire, that its validity and reliability had been previously established by the research team, was used in collecting the data. The data then analyzed using the chi-square test and multinomial logistic regression. Results: A highly significant correlation was observed for maternal age, parity, and family income. Conversely, the variables of education, occupation, and maternal knowledge had no significant correlation. The multivariate test results showed that age could increase the stunting occurrence by 1.084 times (OR = 1.084, 95%CI: 0.256-97.697), while the income factor increased the stunting risk by 2.153 times (OR = 2.153, 95%CI: 0.056-8.822). Conclusion: Stunting in children under five is influenced by maternal age, parity, and family economic status. Healthy reproductive age and having fewer children reduce the risk of stunting. Conversely, maternal education, knowledge, and employment do not have a significant impact. Low economic conditions are the primary factor increasing the risk of stunting.